Reconstructing vegetation diversity in coastal landscapes - Schepers, Mans 1983- (Advances in archaeobotany, 2014)
"This dissertation delves into the reconstruction of past vegetation at the most detailed level. It is not the objective to focus solely on the developments in vegetation over time, but to create an image of the landscape that must have been visible to prehistoric people. Landscape and vegetation form a major starting point for the opportunities available in a certain area for a broad scale of human activities including grazing of livestock, cultivating crops and collecting wild plants. The majority of the analyses are based on seeds and fruits (botanical macroremains) from two Dutch prehistoric regions. These are the small river system in the present Flevopolder, home to settlements of the so-called Swifterbant Culture in the Neolithic period (4300 ‒ 4000 BC), and the Frisian-Groningen terp region in the period prior to the endikements (700 BC ‒ c. 1200 AD)."